2006
DOI: 10.1111/j.1365-2141.2006.06375.x
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of apoptosis genes allows for clinical stratification of primary nodal diffuse large B‐cell lymphomas

Abstract: Summary Intrinsic resistance of lymphoma cells to apoptosis is a probable mechanism causing chemotherapy resistance and eventual fatal outcome in patients with diffuse large B cell lymphomas (DLBCL). We investigated whether microarray expression profiling of apoptosis related genes predicts clinical outcome in 46 patients with primary nodal DLBCL. Unsupervised cluster analysis using genes involved in apoptosis (n = 246) resulted in three separate DLBCL groups partly overlapping with germinal centre B‐lymphocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
48
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 41 publications
6
48
0
Order By: Relevance
“…Consistent with our previous expression microarray results (18) and with a previous study by Davis et al (28), we have found that cases with high levels of proapoptotic and antiapoptotic genes are frequently clinically refractory to chemotherapy. Although the association between high expression levels of antiapoptotic genes and a poor response to chemotherapy has been shown by many other studies (2 -4, 10 -12), the high expression levels of proapoptotic genes in chemotherapy-resistant cases were unexpected.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with our previous expression microarray results (18) and with a previous study by Davis et al (28), we have found that cases with high levels of proapoptotic and antiapoptotic genes are frequently clinically refractory to chemotherapy. Although the association between high expression levels of antiapoptotic genes and a poor response to chemotherapy has been shown by many other studies (2 -4, 10 -12), the high expression levels of proapoptotic genes in chemotherapy-resistant cases were unexpected.…”
Section: Discussionsupporting
confidence: 93%
“…Using microarray expression analysis, we have recently shown that a subset of chemotherapy-refractory DLBCL is characterized by high expression levels of proapoptotic genes, particularly genes that are under transcriptional control of p53 and are involved in the intrinsic, caspase-9 -mediated apoptosis pathway (18). These DLBCL samples were also characterized by high expression levels of apoptosis-inhibiting genes, providing an explanation of why expression of proapoptotic genes does not result in effective induction of apoptosis.…”
mentioning
confidence: 99%
“…This suggestion is supported by the observation that resistance to chemotherapy in DLBCL may be linked to upregulation of anti-apoptotic NF-κB regulated genes, including Bcl-2 and XIAP. The potential importance of investigating such approaches to DLBCL sub-classification has been highlighted in recent publications, which have addressed this subject (32,33). Specific IAP proteins (cIAP1, cIAP2 and XIAP) have been shown to be differentially regulated in a variety of lymphomas, including DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…cDNA synthesis, hybridization and scanning were performed as described previously. [27][28][29] To investigate reproducibility of the hybridizations, technical replicates were included of RNA isolated from primary keratinocytes (EK2000-12), SiHa cells and the FK16A#6 hybrid MCF15cl8. The resulting expression profiles of each of the replicates were highly comparable.…”
Section: Rna Isolationmentioning
confidence: 99%
“…These findings underline the reliability of the data obtained, as was also found in previous studies in which validation of the same micro array platform has been described. [28][29][30] …”
Section: Rna Isolationmentioning
confidence: 99%